2006
DOI: 10.1016/j.str.2005.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Serendipitous Discovery and X-Ray Structure of a Human Phosphate Binding Apolipoprotein

Abstract: We report the serendipitous discovery of a human plasma phosphate binding protein (HPBP). This 38 kDa protein is copurified with the enzyme paraoxonase. Its X-ray structure is similar to the prokaryotic phosphate solute binding proteins (SBPs) associated with ATP binding cassette transmembrane transporters, though phosphate-SBPs have never been characterized or predicted from nucleic acid databases in eukaryotes. However, HPBP belongs to the family of ubiquitous eukaryotic proteins named DING, meaning that pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
116
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 85 publications
(128 citation statements)
references
References 50 publications
8
116
0
4
Order By: Relevance
“…Van Dorsselaer & E. Chabriere, in preparation). The crystallographic structure of HPBP complexed with a phosphate ion confirmed that the DING-protein family is related to PstS proteins and adopts the characteristic 'Venus flytrap' motif (Morales et al, 2006). Interestingly, some Pseudomonas species, but to our knowledge no other bacteria, have been shown to express DING proteins that are more homologous to eukaryotic DINGs (Berna et al, 2007).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Van Dorsselaer & E. Chabriere, in preparation). The crystallographic structure of HPBP complexed with a phosphate ion confirmed that the DING-protein family is related to PstS proteins and adopts the characteristic 'Venus flytrap' motif (Morales et al, 2006). Interestingly, some Pseudomonas species, but to our knowledge no other bacteria, have been shown to express DING proteins that are more homologous to eukaryotic DINGs (Berna et al, 2007).…”
Section: Introductionmentioning
confidence: 74%
“…A 38 kDa DING protein was isolated from breast carcinoma cells by genisteinagarose affinity chromatography (Belenky et al, 2003). Human phosphate-binding protein (HPBP), the first DING protein to also be identified as a phosphate-binding protein, was purified from a human plasma lipoprotein fraction (Morales et al, 2006). The first plant DING was identified in tobacco by virtue of its strong binding to an Arabidopsis thaliana germin-like protein (Berna et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The pstS and the HPBP structures fit a model known as the ''Venus flytrap'', in which two globular domains hinge together to form the phosphate-binding site, with eight conserved residues Hbonding to phosphate [5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…HPBP is a novel member of the DING family of proteins, which are likely ubiquitous in eukaryotes. In humans, DING protein had been identified from synovial fluid of rheumatoid arthritis (Hain et al, 1996;Blass et al, 1999), breast cells (Belenky et al, 2003) and kidney epithelial cells (Kumar et al, 2004), but the first structure was deduced from the HPBP concomitantly purified with PON1 from human serum (Morales et al, 2006). The structure clearly showed a relationship between HPBP and ABC (ATP binding cassette transmembrane) transporters in prokaryotes.…”
Section: Resultsmentioning
confidence: 99%
“…HPBP was first purified by chance along with PON1. HPBP is a member of the DING family, which suggests its distribution in a wide number of eukaryotes (Morales et al, 2006(Morales et al, , 2007. The DING protein family seems to have emerged by consensus for ubiquitous but genetically elusive proteins, usually with a molecular weight of around 40 kDa, of which the N-terminal sequence is DINGGG- (Adams et al, 2002).…”
Section: Introductionmentioning
confidence: 99%